Water and rock : how the Grand Canyon formed - Emminizer, Theresa (Earth's history through rocks., 2020)
Examines how the force of moving water and rock formed the Grand Canyon, discussing the layers of rocks, their ages, and the fossils found there. Also explores the canyon's conservation and ecological importance. Includes color photographs, a glossary, and online resources.